On "Pestilences" in an Ancient Vietnamese Medical Book, Nan Yao Shen Xiao (《南药神效》Miraculous Vietnamese Medicine) - Lina Yang; Jihao Li; Li Shang (Wolters Kluwer Health/LWW, 2020)
Nan Yao Shen Xiao (《南药神效》Miraculous Vietnamese Medicine) is "an ancient Vietnamese medical book in Chinese language" that is extant in Vietnam and plays an important part in Vietnamese medical development history. In the chapter of "Pestilences," the characteristics, prevention, and treatment of pestilences were described in detail. By comparing Miraculous Vietnamese Medicine with Chinese medical books including Ben Cao Gang Mu (《本草纲目》Compendium of Materia Medica), it can be seen that the prevention and treatment of pestilences were profoundly influenced by Chinese medical books. The folk-proven prescriptions in Compendium of Materia Medica, Zhou Hou Bei Ji Fang (《肘后备急方》Handbook of Prescriptions for Emergency), Bei Ji Qian Jin Yao Fang (《备急千金要方》Important Prescriptions Worth a Thousand Gold for Emergency), and other Chinese medical books were included directly or after adaptation (slight modification in dosage and usage) in Miraculous Vietnamese Medicine. This form of "foreign acceptance" witnessed the history of medical culture communication between China and Vietnam, expanded the application scope of Chinese medicine in prevention and treatment of pestilences in a foreign land, promoted the overseas spread of folk-proven prescriptions in Chinese medicine to treat pestilences, and played a major part in treatment and prevention of disease in ancient Vietnam.